(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is dedicated to the topic "The Importance of Local Raw Materials and Local Suppliers in Reducing Enterprise Costs." It examines the significance of effective cost management for enterprises and the advantages of utilizing local resources. The article highlights opportunities for reducing costs, minimizing transportation expenses, and fostering the local economy by engaging local raw materials and suppliers. Additionally, it discusses the social and economic benefits of collaborating with local producers and their role in achieving sustainable development goals. The findings suggest that leveraging local resources not only helps enterprises reduce costs but also enhances their competitiveness.